Comparison of fractional flow reserve and instantaneous wave-free ratio for the hemodynamic assessment of jailed side branches in bifurcation stenting. (25th November 2020) - Altstidl, J.M; Marwan, M; Troebs, M; Achenbach, S; Gaede, L
Abstract: Background: Provisional side-branch stenting strategy is one of the preferred strategies for treatment of bifurcation lesions. Whereas using fraction flow reserve (FFR) for the physiologic assessment of jailed side branches is well studied, the reliability of resting indices such as instantaneous wave free ratio (iFR) is unknown. Methods: Consecutive patients with provisional stenting of a bifurcation and a jailed side branch were enrolled in this study. FFR and iFR were measured and, after assuring absence of baseline shift and drift, both measurements were repeated after 3 minutes. Hyperemia was induced by intra-coronary adenosine with a dose of 48μg for the right coronary artery and 96μg for the left coronary artery. Cut-off for the assumed functional significance of a stenosis was 0.80 for FFR and 0.89 for iFR. The decision to treat the side branch was left to the interventionalist's discretion. Results: 37 jailed side branches in 36 patients (age 68.4±8.2; male 81% (n=29)) were consecutively enrolled in the study. The main vessel was the left main in 3% (n=1), the left anterior descending (LAD) in 65% (n=24), the diagonal branch (D1) in 3% (n=1), the left circumflex artery (LCX) in 24% (n=9) and the right coronary artery (RCA) in 5% (n=2). The Medina classification revealed true bifurcation stenosis defined as Medina 1–1-1 prior to treatment in 35% (n=13). FFR showed 35% (n=13) of the stenosis to be functionally significant with a high reproducibility of the results (r=0.986). FFR showed a low correlation with angiographic assessment (r=−0.477). iFR indicated hemodynamic relevance in 38% of lesions (n=14) with a high reproducibility (r=0.967) and also correlated poorly with angiographic assessment (r=−0.271). iFR was found to closely correlate with FFR in jailed side branches (r=0.720, Figure 1A). Bland-Altman analysis showed iFR and FFR agreed with a mean difference between FFR and iFR of −0.054±0.146. In 81% (n=30) FFR and iFR showed the same results regarding functional significance. In 8% (n=3) FFR was ≤0.80 and iFR >0.89, in 11% (n=4) FFR was >0.80 and iFR was ≤0.89 (Figure 1B). Side branch treatment was performed in 32% (n=12). All of these lesions showed functional significance in FFR or iFR. Stent implantation was performed in 8% (n=3), balloon angioplasty in 19% (n=7) and balloon angioplasty with a drug-eluting balloon in 5% (n=2). Conclusions: The results of this study confirm the poor correlation of angiographic and functional assessment of coronary artery stenoses. Our data show close agreement of iFR and FFR in stent-jailed side branches. Therefore, iFR can be considered as a reliable technique for guidance of provisional side branch stenting. Funding Acknowledgement: Type of funding source: None